2013
DOI: 10.1248/bpb.b13-00290
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Responses of Procaterol and CD38 Inhibitors in an Ozone-Induced Airway Hyperresponsiveness Mice Model

Abstract: Airway hyperresponsiveness (AHR) and airway inflammation are key pathophysiological features of many respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD). To evaluate the treatment responses of procaterol and CD38 inhibitors in an ozone-induced AHR mice model, we hypothesized that procaterol and two synthetic CD38 inhibitors (Compounds T and H) might have therapeutic effects on the ozone-induced AHR mice model, and the nuclear factor-kappaB (NF-κB) pathway and the CD38 enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This is most like due to the membrane permeability of the drugs, which allow them to concentrate within the cells (Dong, et al, 2011). Deng et al tested compound 4 from this study in an ozone-induced airway hyperresponiveness mouse model and found that it was not effective (Deng, et al, 2013). …”
Section: Design and Characterization Of Cd38 Inhibitorsmentioning
confidence: 98%
“…This is most like due to the membrane permeability of the drugs, which allow them to concentrate within the cells (Dong, et al, 2011). Deng et al tested compound 4 from this study in an ozone-induced airway hyperresponiveness mouse model and found that it was not effective (Deng, et al, 2013). …”
Section: Design and Characterization Of Cd38 Inhibitorsmentioning
confidence: 98%